Rationale for Vaccination against COVID-19 among Elderly and Senile People with Comorbid Conditions - M. P. Kostinov; Chen Zhang; I. A. Khrapunova; A. S. Pechenik; V. A. Brazhnik; V. A. Utkin; M. N. Laktionova; A. V. Linok; S. P. Raicic (Эпидемиология и вакцинопрофилактика)
Relevance. COVID-19 vaccination reduces mortality and the course of severe diseases. However, there is an insufficiency of studies evaluating factors leading to infection among COVID-19 vaccinated individuals.Aim. Identification of epidemiological features that distinguish cases of the disease in vaccinated and unvaccinated cohorts.Materials and methods. The analysis of the incidence of COVID-19 in 1126 hospitalized patients in the period from 23.06.2021 to 01.05.2022 was carried out taking into account the presence or absence of vaccination against the SARS-CoV-2 virus.Results. It was found that the risk of COVID-19 getting sick in the unimmunized was 1.5 times higher than in the vaccinated (p < 0.05). The incidence of hospitalization, due to the severity of the condition (moderate, severe and extremely severe), in unvaccinated people with no history of comorbidities, is more than 3 times higher than in vaccinated people (p < 0.05) in the same group. The probability of death from COVID-19 among vaccinated people is 1.5 times lower than among unimmunized people (p < 0.05). The age characteristic of mortality in vaccinated people shifts to the «senile» age (76.93 ± 1.32), while among the unimmunized, the age of death is closer to the category of «elderly» (73.74 ± 1.39 years) (p ≤ 0.05). In the structure of mortality among the vaccinated, the main share was made up of patients with a history of 3 to 7 concomitant systemic diseases (66.7%), while among the unvaccinated, the main share (74.5%) were patients either without comorbidities or with a history of 1 to 2 concomitant diseases.Conclusion. The results of the epidemiological features of the COVID-2 epidemic process have shown that vaccination against the SARS-CoV-2 virus is vital for elderly and senile people with comorbid conditions.